Cholinergic Enhancement of Cell Proliferation in the Postnatal Neurogenic Niche of the Mammalian Spinal Cord. (26th June 2015) - Corns, Laura F.; Atkinson, Lucy; Daniel, Jill; Edwards, Ian J.; New, Lauryn; Deuchars, Jim; Deuchars, Susan A.
Abstract The region surrounding the central canal (CC) of the spinal cord is a highly plastic area, defined as a postnatal neurogenic niche. Within this region are ependymal cells that can proliferate and differentiate to form new astrocytes and oligodendrocytes following injury and cerebrospinal fluid contacting cells (CSFcCs). The specific environmental conditions, including the modulation by neurotransmitters that influence these cells and their ability to proliferate, are unknown. Here, we show that acetylcholine promotes the proliferation of ependymal cells in mice under both in vitro and in vivo conditions. Using whole cell patch clamp in acute spinal cord slices, acetylcholine directly depolarized ependymal cells and CSFcCs. Antagonism by specific nicotinic acetylcholine receptor (nAChR) antagonists or potentiation by the α7 containing nAChR (α7*nAChR) modulator PNU 120596 revealed that both α7*nAChRs and non‐α7*nAChRs mediated the cholinergic responses. Using the nucleoside analogue EdU (5‐ethynyl‐2'‐deoxyuridine) as a marker of cell proliferation, application of α7*nAChR modulators in spinal cord cultures or in vivo induced proliferation in the CC region, producing Sox‐2 expressing ependymal cells. Proliferation also increased in the white and grey matter. PNU 120596 administration also increased the proportion of cells coexpressing oligodendrocyte markers. Thus, variation in the availability of acetylcholine can modulate the rate of proliferation of cells in the ependymal cell layer and white and grey matter through α7*nAChRs. This study highlights the need for further investigation into how neurotransmitters regulate the response of the spinal cord to injury or during aging. Stem Cells2015;33:2864–2876